2014
DOI: 10.1108/jd-01-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the flood: when more of a dose is less

Abstract: Purpose -The purpose of this paper is to explore the flood of information that is inundating us. This flood makes it increasingly difficult to make sense of the world and arrive at the correct interpretation of events. Design/methodology/approach -Classic narrative literature review applying the dosage metaphor to the growing problem of information overload. Findings -The seven elements of dosage -amount, frequency, sequencing, delivery systems, contraindications, interactions, and dysfunctions -are used to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…It has been suggested that the magnitude of the information available has created a situation characterised by ambiguity, uncertainty and lack of trust (see, Beck, 1992;Benigeri & Pluye, 2003;Giddens, 1997). "Information overload" has become a central concept in areas such as sociology, psychology and communication science (Savolainen, 2007), and it generally highlights that the supply of information is greater than our capacity to process it (Eppler & Mengis, 2004;Johnson, 2014).…”
Section: With This Development As Backdropmentioning
confidence: 99%
“…It has been suggested that the magnitude of the information available has created a situation characterised by ambiguity, uncertainty and lack of trust (see, Beck, 1992;Benigeri & Pluye, 2003;Giddens, 1997). "Information overload" has become a central concept in areas such as sociology, psychology and communication science (Savolainen, 2007), and it generally highlights that the supply of information is greater than our capacity to process it (Eppler & Mengis, 2004;Johnson, 2014).…”
Section: With This Development As Backdropmentioning
confidence: 99%
“…The literature considering psychological and cognitive coping strategies with information overload acknowledge individual, social and organisational strategies. The described individual strategies include (selective) attention, delegation (gatekeeping), escape and creative destruction (Johnson, 2014), filtering, withdrawal (Savolainen, 2007), queueing (Wilson, 1995) and developing information competencies to gain control over the information and technology environment (Bawden and Robison, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Selective attention described by Johnson (2014) has certain similarities with the filtering strategy. This strategy focuses on when to stop seeking and filtering relevant information while experiencing excessive floods of information.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations